A randomized clinical trial on the acute therapeutic effect of TRPA1 and TRPM8 agonists in patients with oropharyngeal dysphagia. Issue 6 (16th February 2020) - Tomsen, Noemí; Alvarez‐Berdugo, Daniel; Rofes, Laia; Ortega, Omar; Arreola, Viridiana; Nascimento, Weslania; Martin, Alberto; Cabib, Christopher; Bolivar‐Prados, Mireia; Mundet, Lluís; Legrand, Coline; Clavé, Pere; et al.
Abstract: Background: Oropharyngeal dysphagia (OD) treatment is moving away from compensatory strategies toward active treatments that improve swallowing function. The aim of this study was to assess the acute therapeutic effect of TRPA1/M8 agonists in improving swallowing function in OD patients. Methods: Fifty‐eight patients with OD caused by aging, stroke, or neurodegenerative disease were included in a three‐arm, quadruple‐blind, randomized clinical trial (NCT02193438). Swallowing safety and efficacy and the kinematics of the swallow response were assessed by videofluoroscopy (VFS) during the swallow of 182 ± 2 mPa·s viscosity (nectar) boluses of a xanthan gum thickener supplemented with (a) 756.6 μmol/L cinnamaldehyde and 70 μmol/L zinc (CIN‐Zn) (TRPA1 agonists), (b) 1.6 mmol/L citral (CIT) (TRPA1 agonist), or (c) 1.6 mmol/L citral and 1.3 mmol/L isopulegol (CIT‐ISO) (TRPA1 and TRPM8 agonists). The effects on pharyngeal event‐related potentials (ERP) were assessed by electroencephalography. Key Results: TRPA1 stimulation with either CIN‐Zn or CIT reduced time to laryngeal vestibule closure (CIN‐Zn P  = .002, CIT P  = .023) and upper esophageal sphincter opening (CIN‐Zn P  = .007, CIT P  = .035). In addition, CIN‐Zn reduced the penetration‐aspiration scale score ( P  = .009), increased the prevalence of safe swallows ( P  = .041), and reduced the latency of the P2 peak of the ERP. CIT‐ISO had no positive effect on biomechanics or neurophysiology. No significant adverse events were observed. Conclusions and Inferences: TRPA1 stimulation with CIN‐Zn or CIT improves the swallow response which, in the case of CIN‐Zn, is associated with a significant improvement in cortical activation and safety of swallow. These results provide the basis for the development of new active treatments for OD using TRPA1 agonists. Abstract : Methodology used in the manuscript includes the videofluoroscopy (VFS) to evaluate VFS signs of safety and efficacy of swallow, and the timing of the oropharyngeal swallow response; and pharyngeal sensory evoked potentials (PSEP) to electrical stimulation to measure the latency and amplitude of PSEP peaks.